2021
DOI: 10.3390/polym13030331
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Improvement between PE and PA in Multilayer Rotational Molding

Abstract: The aim of this study is to investigate a multilayer structure made of polyethylene and polyamide by rotational molding. Due to the different polarity of these polymers, it is difficult to ensure enough adhesion between created layers. Two methods leading to improve adhesion are introduced. Plasma modification of polyethylene powder, after which new functional groups are bound to the treated surface, may enhance specific adhesion by forming hydrogen bonds with-CONH groups of polyamide. Different strategies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The other combinations (13P, 13N, 15P, and 15N) follow the same principle. In previous studies, it was shown that oxygen-plasma-treated Dowlex TM 2629.10UE had good wettability, which enhanced the adhesion of matrix with fillers [ 3 , 8 ]. It was evident from the SEM results shown in Figure 3 that the plasma treatment of PE enhanced the adhesion behavior of non-polar polyethylene polymer by providing better chemical interaction and mechanical interlock in the matrix.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other combinations (13P, 13N, 15P, and 15N) follow the same principle. In previous studies, it was shown that oxygen-plasma-treated Dowlex TM 2629.10UE had good wettability, which enhanced the adhesion of matrix with fillers [ 3 , 8 ]. It was evident from the SEM results shown in Figure 3 that the plasma treatment of PE enhanced the adhesion behavior of non-polar polyethylene polymer by providing better chemical interaction and mechanical interlock in the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of these polar groups induced creation of polymer chains with free radicals, making it possible to add or interlock functional groups to the surface of the polymers. This would have had a favorable impact on the polymer surface activation by increasing the adhesive nature of the composites [ 3 , 8 ]. Agglomeration of carbon fibers resulted in reduction in the flexural properties of the polymer composites [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where n is the number of experiments; p is the number of input (independent) parameters; i is the serial number of the experiment; y i is the actual value of the output parameter in the i experiment; yc i is the calculated value of the output parameter, calculated using a multifactor mathematical model, for the conditions (values of input parameters) of the i experiment; and ym is the average value of the actual value of the output parameter for all n experiments (the general average). Using the obtained particular dependencies, shown in Figures 12-14, a multifactor mathematical model (7) was built based on the generalized Protodyakonov Equation (5) as follows:…”
Section: Development Of a Mathematical Modelmentioning
confidence: 99%
“…Products obtained via the rotational molding of plastics are characterized by a long service life, chemical resistance, and low cost [ 4 , 5 , 6 ]. At present, the development of new formulations based on various polymers [ 7 , 8 , 9 , 10 ] and fillers for rotational molding is being carried out at an accelerated pace; compositions with clay [ 11 , 12 ], quartz [ 13 ], halloysite [ 14 ], glass fiber or powder [ 15 , 16 , 17 ], copper slag [ 18 ], or graphite [ 19 , 20 ] have also been proposed.…”
Section: Introductionmentioning
confidence: 99%